Optimising the future of technology in organisations: A human factors perspective. Issue 3 (August 2020) - Wiggins, Mark W; Auton, Jaime; Bayl-Smith, Piers; Carrigan, Ann
New technologies are critical for sustained economic growth in contemporary organisations. However, the success of new technologies is dependent upon the relationship with users. Using a human factors framework, this article examines contemporary approaches to the assessment of human–technology interactions, highlighting the lack of integration and the need for a comprehensive approach that considers user contributions, including skills, capabilities and dispositions; technological contributions, including dependencies, reliability, complexity, and accuracy; and organisational contributions through training assessment, organisational climate and culture, and leadership. The successful integration of new technologies in the workplace is likely to lead to a more productive and enjoyable interaction for employees and customers, together with systems that are more resilient to the complexities and threats that are likely to emerge in the future work environment. JEL Classification:J28, L15, D23, D24